1997
DOI: 10.1017/s0003480097006477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic history of cystic fibrosis mutations in Italy. I. Regional distribution

Abstract: Earlier analysis of the Italian population showed patterns of genetic differentiation that were interpreted as being the result of population settlements going back to pre-Roman times. DNA disease mutations may be a powerful tool in further testing this hypothesis since the analysis of diseased individuals can detect variants too rare to be resolved in normal individuals. We present data on the relative frequencies of 60 cystic fibrosis (CF) mutations in Italy and the geographical distribution of the 12 most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 0 publications
2
43
1
1
Order By: Relevance
“…This condition is fulfilled if f obs -2.5SE is greater than the threshold. In the case of CF in southern Europe, the threshold is 0.004, since the global frequency of CF mutations in Europe is about 0.02, that of ∆F508 is about 0.01 in Italy (Bonizzato et al 1994;Rendine et al 1997), in Southern France (Claustres et al 1993), and in Spain (Estivill et al 1997), and the combined frequency of the other most common CF mutations is about 0.006. Therefore the probability that a C mutation is classified as being common (hence non-CF-causing) was calculated as follows: f obs must be at least equal to 0.004+2.5SE; this value f minimal is 0.025, 0.015, 0.012, and 0.009 when N is 380, 1000, 1500, and 3000, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is fulfilled if f obs -2.5SE is greater than the threshold. In the case of CF in southern Europe, the threshold is 0.004, since the global frequency of CF mutations in Europe is about 0.02, that of ∆F508 is about 0.01 in Italy (Bonizzato et al 1994;Rendine et al 1997), in Southern France (Claustres et al 1993), and in Spain (Estivill et al 1997), and the combined frequency of the other most common CF mutations is about 0.006. Therefore the probability that a C mutation is classified as being common (hence non-CF-causing) was calculated as follows: f obs must be at least equal to 0.004+2.5SE; this value f minimal is 0.025, 0.015, 0.012, and 0.009 when N is 380, 1000, 1500, and 3000, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, analysis of numerous mutations is required to obtain satisfactory carrier detection levels. 4 Based on published manuscripts [5][6][7] and the results of a survey of the various CF molecular genetic laboratories (European Concerted Action BMH4-CT96-0462, unpublished data (M Macek Jr, C Deltas, P Pachecco, (1999), personal communication)) we recommend a minimal number of mutations be assembled for each ethnic population (or region) to ensure detection of disease mutations in at least 80% of all carriers and patients (Tables 1 and 2). CF mutation detection methods can be divided into two groups: mutation detection (test DNA sample for presence or absence of one specific mutation), and mutation scanning methods (screen sample for any deviation from the standard sequence).…”
Section: Methodsmentioning
confidence: 99%
“…N1303K and G542X occur at a frequency of around 5% in Italy. 11 In Germany, a study of 658 CF families revealed mutation frequencies of R553X (1.8%), N1303K (1.3%), G542X (1.1%), G551D (0.8%) and R347P (0.8%). 12 The frequency of CFTR mutations recorded for just over 1000 patients for the Irish CF Database include G551D in 7%, R117H in 2% and DF508 in 72% of patients.…”
Section: Cftr Mutations In Caucasiansmentioning
confidence: 99%